2023
DOI: 10.3390/molecules28196792
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Mono-Cyclopentadienyl Titanium and Rare-Earth Metal Catalysts for the Production of Syndiotactic Polystyrene

Bo Wen,
Hongfan Hu,
Di Kang
et al.

Abstract: Syndiotactic polystyrene (SPS) refers to a type of thermoplastic material with phenyl substituents that are alternately chirally attached on both sides of an aliphatic macromolecular main chain. Owing to its excellent physical and mechanical properties, as well as its chemical stability, high transparency, and electrical insulation characteristics, SPS is used in a wide variety of technical fields. SPS is commonly produced via the stereoselective transition metal-catalyzed coordination polymerization method me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…In the last two decades, precisely controlled polymerization of styrene and its derivatives had made significant progress by using rare-earth metal catalysts. A variety of well-defined rare-earth metal catalysts sprung up, which showed high activity and perfect regioselectivity in both the homo- and copolymerization of styrene monomers. The first examples of highly syndiospecific styrene polymerization mediated by rare-earth metal was reported almost simultaneously by the groups of Hou and Carpentier. , Cui’s group designed a series of constrained-geometry-configuration (CGC) type rare-earth metal complexes, which behaved well in styrene polymerization. , More interestingly, these complexes exhibited excellent performances in the polymerization of polar styrene monomers. , Isotactic polymerization of styrene monomers can be achieved by rare-earth metal catalysts as well. Carpentier et al first reported the highly isotactic polymerization of styrene initiated by rare-earth metal complexes in 2007 .…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, precisely controlled polymerization of styrene and its derivatives had made significant progress by using rare-earth metal catalysts. A variety of well-defined rare-earth metal catalysts sprung up, which showed high activity and perfect regioselectivity in both the homo- and copolymerization of styrene monomers. The first examples of highly syndiospecific styrene polymerization mediated by rare-earth metal was reported almost simultaneously by the groups of Hou and Carpentier. , Cui’s group designed a series of constrained-geometry-configuration (CGC) type rare-earth metal complexes, which behaved well in styrene polymerization. , More interestingly, these complexes exhibited excellent performances in the polymerization of polar styrene monomers. , Isotactic polymerization of styrene monomers can be achieved by rare-earth metal catalysts as well. Carpentier et al first reported the highly isotactic polymerization of styrene initiated by rare-earth metal complexes in 2007 .…”
Section: Introductionmentioning
confidence: 99%